Cytotoxicity of oxidised Low Density Lipoprotein (OxLDL) on U937 cells: a comparison of viability measurement by propidium iodide-flow cytometry and MTT reduction assays / Mohd Izani Othman, Steven Gieseg and Barry Hock - Othman, Mohd Izani; Gieseg, Steven; Hock, Barry (2016)
Atherosclerosis is a major cause of cardiovascular disease. It is characterised by a development of atherosclerotic plaque in a blood vessel wall that involves a death of macrophages. Oxidized low density lipoprotein (oxLDL) is a toxic and a key player that promotes macrophages recruitment, activation, and foam cell formation in atherosclerotic inflammation. Thus, an understanding of the underlying mechanism of cell death is important to gather information for therapeutic interventions. In vitro studies, using cells are common for toxicity investigation where cell viability is measured. While there are different options of assays available for cell viability measurement, choosing the most appropriate assay could be a challenging task. Therefore, picking the right and the best assay tool to suit particular needs requires an understanding of what each assay measures as well as limitations of the assay chemistries. This is significant to generate meaningful data obtained from the experiments. In this study, two cell viability assays i.e. MTT reduction assay and PI-flow cytometry assay were compared.